PENDIDIKAN KARAKTER MELALUI PRAMUKA: IMPLEMENTASI DASA DARMA DI USIA SEKOLAH DASAR - Siti Fadma Wati; Muhamad Sofian Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of Scout activities in shaping the character values of elementary school students, especially in Tangerang City. Using survey and experimental methods, data were collected through questionnaires, observations, and measurements of pretests-postes on students involved in Scout activities. The results of the study show that Scout activities significantly increase character values such as discipline, responsibility, cooperation, and leadership. The experimental class that intensively participated in Scout activities showed a higher increase in character values compared to the control class. Activities such as group games, leadership simulations, and outdoor exploration provide hands-on experiences that help students understand and apply these values in everyday life. In addition, social interaction during Scout activities also increases empathy, tolerance, and communication skills between students. A survey of teachers and parents revealed that 85% of respondents considered Scout activities to be very effective in shaping students' character. The results of this study confirm that Scouting is not only an additional activity, but also an important instrument in character education in the modern era. The values contained in the Trisatya and Dasa Darma become moral guidelines that are applied through real practice. These findings contribute to the development of a more holistic character education curriculum that is relevant to today's challenges. Further research is suggested to expand the scope and explore new methods in the integration of Scout activities with formal education.